Understanding sociology - Calhoun, Craig J., 1952- (McGraw - Hill, 1995)
[The authors] have tried to make this a book students will want to read as well as a book from which they will learn about the best of contemporary and classical sociology.... The concepts of functional integration, power, social action, social structure, and culture are presented as major tools of sociological work.--Pref.